From farm to plate: Spatio-temporal characterization revealed compositional changes and reduced retention of γ-oryzanol upon processing in rice - Ghosh, Swarnadip; Bollinedi, Haritha; Gopala Krishnan, S.; Kundu, Aditi; Singh, Anupama; Bhowmick, Prolay Kumar; Singh, Archana; Nagarajan, Mariappan; Vinod, Kunnummal Kurungara; Ellur, Ranjith Kumar; Singh, Ashok Kumar (Frontiers in Nutrition, 2022)
Background: Antioxidants detain the development and proliferation of various non-communicable diseases (NCDs). γ-oryzanol, a group of steryl ferulates and caffeates, is a major antioxidant present in rice grain with proven health benefits. The present study evaluated the distribution and dynamics of γ-oryzanol and its components in spatial and temporal scales and also delineated the effect of processing and cooking on its retention. Methods: Six rice varieties (four Basmati and two non-Basmati) belonging to indica group were analyzed at spatial scale in four different tissues (leaf blades, leaf sheaths, peduncle and spikelets) and temporal scale at three developmental stages (booting, milky and dough). Additionally, the matured grains were fractioned into husk, embryo, bran, and endosperm to assess differential accumulation in these tissues. Further, milling and cooking of the samples was done to assess the retention upon processing. After extraction of γ-oryzanol by solvent extraction method, individual components were identified by UPLC-QToF-ESI-MS and quantified by RP-HPLC. Results: The non-seed tissues were significantly different from the seed tissues for composition and quantitative variation of γ-oryzanol. Cycloartenyl caffeate was predominant in all the non-seed tissues during the three developmental stages while it showed significant reduction during the growth progression towards maturity and was totally absent in the matured grains. In contrary, the 24-methylenecycloartanyl ferulate, campesteryl ferulate, and -sitosteryl ferulate showed significant increment towards the growth progression to maturity. Milling caused a significant reduction, retaining only an average of 58.77% γ-oryzanol. Cooking brown rice in excess water showed relatively lower average retention (43.31%) (excess water) than samples cooked in sufficient water (54.42%). Cooked milled rice showed the least mean retention of 21.66%. Conclusion: The results demonstrate prominent compositional variation of γ-oryzanol during different growth stages. Ferulate esters of γ-oryzanol were predominant in the seed tissues while caffeate esters were dominant in non-seed tissues. Basmati cultivars show differential expression of γ-oryzanol and its components compared to non-Basmati cultivars. Cooking in excess water causes maximum degradation of γ-oryzanol. Post-harvest losses due to milling and cooking indicate the necessity of biofortification for γ-oryzanol content in rice grain.